Improving the Ability of Teachers in Utilizing the Surrounding Environment as a Learning Resource in the Era of the Covid-19 Pandemic Through In-House Training at SD Negeri Banjarharjo, Kalibawang, Kulon Progo in 2021 - Umi Kandibah (International Journal of Chemistry Education Research, 2022)
The research aims to improve the ability of teachers to utilize the surrounding environment as a learning resource and increase the professionalism of school principals in the era of the COVID-19 pandemic. The method used in this research is analytical descriptive, which is a study to collect data, describe, process, analyze, interpret and conclude data so that a systematic picture is obtained. Document data collection, observation, and interviews. The research subjects were 9 teachers of Banjarharjo Public Elementary School, Kalibawang Kulon Progo consisting of 6 class teachers and 3 subject teachers. The data collection in this school action research was carried out using instruments consisting of: 1) an instrument for observing participants' abilities, and 2 ) the ability of researchers in managing IHT. The data analysis used in this research is descriptive quantitative data analysis. The expected target in this study is that teachers are able to utilize learning resources with the surrounding environment. The results of the study on the ability of teachers to use the surrounding environment as a learning resource, it was found that an increase in the average score of the first cycle to the second cycle reached 0.50, while based on the percentage there was an increase of 12.45%, with the last average percentage of the second cycle reaching 87 .89%, thus the level of teacher ability has shown a significant increase above the indicator of success, 85%, when viewed from the results based on the conversion of the average value of the second cycle reaching 4, with the "very good" category. Furthermore, the results of research related to the management of the implementation of In House Training (IHT) by researchers in delivering material using the surrounding environment as a learning resource, the results obtained are the average score in cycle I; 3.29, with a percentage of 82.12%, the conversion value reached; 3, with the "Satisfactory" category, while in the second cycle the research results total average score of 3.59, based on a percentage of 89.65%, value conversion; 4, with the category "Very Satisfactory", when compared to cycle I; there is an increase; 7.53%, if it is concluded that the implementation of IHT can have a positive impact on increasing the ability of participants to utilize learning resources using the surrounding environment.   Keywords: Learning Resources, the surrounding environment, In House Training (IHT)